BACKGROUND PENDIDIK PAUD YANG BERJIWA AHLUSSUNNAH WALJAMA'AH DI KB TBS KUDUS - Anita Afrianingsih; Sholikhah Sholikhah; Lailatuz Zahroh; Istafidatul Mustakhiroh (JCE (Journal of Childhood Education), 2021)
The study aims to determine the description of the performance of the teaching of a teacher's birth control. Education in the Institute introduced and instilled the values of the total understanding of the worshippers to the students. So that they have value, character, and knowledge that is beneficial to religion, nation and country.Â  The collection method data that is used is a library is a method of data collection sourced from the literature, the result of the educators ' observation of planting Jan characters through habituation such as daily prayer activities, Hadist, dzitching, memorization Surah the short, Shalawat Nariyah and the introduction of prayers.